Investigating associations between the physical living environment and hippocampus in adulthood and older age - Johanna Drewelies; Angela Fiedler; Timothy R. Brick; Simone Kühn (Environmental Research, 2025)

Different dissolved organic matter sources sustain microbial life in a sandy beach subterranean estuary – an incubation study - Grace A. Abarike; Simone Brick; Bert Engelen; Jutta Niggemann (Frontiers in Marine Science, 2024)
In subterranean estuaries (STE), fresh and saline groundwater introduce dissolved organic matter (DOM) of different origin. This DOM serves as substrate for microorganisms that thrive in the STE. In high-energy beaches with dynamic porewater advection, microbial communities face frequent changes in groundwater composition, even at several meters depth. It is unknown how DOM from deep STE groundwater (> 5 m depth) is transformed by prevailing microbial communities. To address this question, we performed sediment incubations in flow-through reactors (FTRs) with deep (6 m depth) STE groundwater of low (1.6) and high salinity (29.1). FTR setups were sampled daily for quantification of dissolved organic carbon (DOC), and at start and end (day 13) of the incubation for analysis of DOM composition, microbial cell numbers and community composition. Solid-phase extracted DOM was molecularly characterized via ultrahigh-resolution Fourier-transform ion cyclotron resonance mass spectrometry. Both groundwater types contained mainly reworked DOM. Corroborating its presumed origin, the fresh groundwater had a more terrestrial DOM signature with a higher proportion of aromatic compounds compared to the saline groundwater. Over the course of the incubation, DOC concentrations increased primarily due to leaching of sedimentary organic matter, providing an additional source of DOM. In all setups, the DOM composition changed significantly from start to end, and similarly for fresh and saline groundwater. From the ~2700 molecular formulae (MF) detected on day 0, 34-35% were removed during the incubations, demonstrating the potential of deep STE microbial communities to degrade recalcitrant DOM that is supplied with the advective porewater flow. However, a substantial portion of MF (63-64%) was retained in both groundwater types, indicating that a fraction of deep STE-DOM is resistant to removal. Properties of MF that were newly detected on day 13 (26-28%) were indicative of labile DOM. Some of these newly detected MF were also identified in sediment-leachates, suggesting that beach sediments are a source of fresh DOM for the STE microbial communities. It is likely that due to longer groundwater residence time in the STE, continuous leaching and microbial processing shift the molecular composition of released DOM from more labile to more recalcitrant DOM.

Spatial and temporal dynamics of groundwater biogeochemistry in the deep subsurface of a high-energy beach - Anja Reckhardt; Rena Meyer; Stephan L. Seibert; Janek Greskowiak; Magali Roberts; Simone Brick; Grace Abarike; Kojo Amoako; Hannelore Waska; Kai Schwalfenberg; Iris Schmiedinger; Oliver Wurl; et al. (Marine Chemistry, 2024)

The DynaDeep observatory – a unique approach to study high-energy subterranean estuaries - Gudrun Massmann; Grace Abarike; Kojo Amoako; Felix Auer; Thomas H. Badewien; Cordula Berkenbrink; Michael Ernst Böttcher; Simone Brick; Iris Valeria Medina Cordova; Jairo Cueto; Thorsten Dittmar; Bert Engelen; et al. (Frontiers in Marine Science, 2023)
Subterranean estuaries are connective zones between inland aquifers and the open sea where terrestrial freshwater and circulating seawater mix and undergo major biogeochemical changes. They are biogeochemical reactors that modify groundwater chemistry prior to discharge into the sea. We propose that subterranean estuaries of high-energy beaches are particularly dynamic environments, where the effect of the dynamic boundary conditions propagates tens of meters into the subsurface, leading to strong spatio-temporal variability of geochemical conditions. We hypothesize that they form a unique habitat with an adapted microbial community unlike other typically more stable subsurface environments. So far, however, studies concerning subterranean estuaries of high-energy beaches have been rare and therefore their functioning, and their importance for coastal ecosystems, as well as for carbon, nutrient and trace element cycling, is little understood. We are addressing this knowledge gap within the interdisciplinary research project DynaDeep by studying the combined effect of surface (hydro- and morphodynamics) on subsurface processes (groundwater flow and transport, biogeochemical reactions, microbiology). A unique subterranean estuary observatory was established on the northern beach of the island of Spiekeroog facing the North Sea, serving as an exemplary high-energy research site and model system. It consists of fixed and permanent infrastructure such as a pole with measuring devices, multi-level groundwater wells and an electrode chain. This forms the base for autonomous measurements, regular repeated sampling, interdisciplinary field campaigns and experimental work, all of which are integrated via mathematical modelling to understand and quantify the functioning of the biogeochemical reactor. First results show that the DynaDeep observatory is collecting the intended spatially and temporally resolved morphological, sedimentological and biogeochemical data. Samples and data are further processed ex-situ and combined with experiments and modelling. Ultimately, DynaDeep aims at elucidating the global relevance of these common but overlooked environments.